2014
DOI: 10.1136/jech-2014-204009
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighbourhood social cohesion and myocardial infarction

Abstract: Background The main strategy for alleviating heart disease has been to target individuals and encourage them to change their health behaviors. Though important, emphasis on individuals has diverted focus and responsibility away from neighborhood characteristics, which also strongly influence people’s behaviors. Although a growing body of research has repeatedly demonstrated strong associations between neighborhood characteristics and cardiovascular health, it has typically focused on negative neighborhood char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 42 publications
2
48
1
1
Order By: Relevance
“…In western countries, evidence has shown similar results. Adults in the United States without cardiovascular disease who perceived higher neighbourhood social cohesion presented a reduced likelihood of incident myocardial infarction over 4 years ( 80 ).…”
Section: Heart and Stress Systemmentioning
confidence: 99%
“…In western countries, evidence has shown similar results. Adults in the United States without cardiovascular disease who perceived higher neighbourhood social cohesion presented a reduced likelihood of incident myocardial infarction over 4 years ( 80 ).…”
Section: Heart and Stress Systemmentioning
confidence: 99%
“…A growing body of research suggests that neighborhood characteristics impact a wide range of health behaviors and outcomes. 516 However, research in this area has historically emphasized the impact of negative neighborhood characteristics (e.g., violence, density of fast food restaurants, noise, traffic, poor air quality, vandalism, drug use, and physical decay) on worsening health. 17,18 Fewer studies have examined the role that positive neighborhood characteristics, such as neighborhood social cohesion, play in enhancing health.…”
Section: Introductionmentioning
confidence: 99%
“…510 Furthermore, a growing number of studies have linked neighborhood social cohesion with intermediate behavioral outcomes such as increased physical activity, 1214 increased number of smoking quit attempts, and increased smoking cessation. 15,16 The theoretic orientation of this study is informed by the social ecologic model, which in turn emerged from developments in several fields, including community psychology, urban sociology, and public health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that neighborhood factors have an impact on various health outcomes and health behaviors ( Ellen et al, 2001 , Feldman and Steptoe, 2004 ). Specifically, perceived neighborhood social cohesion, which is generally defined as the solidarity and connectedness within a group of individuals ( Sampson et al, 1997 , Kandula et al, 2009 ), at high levels has been shown to be protective against adverse health outcomes such as hypertension, myocardial infarction, stroke mortality ( Clark et al, 2011 , Kim et al, 2014 , Kim et al, 2013 , Mujahid et al, 2008 ) and to be related to positive health behaviors such as greater physical activity ( Echeverría et al, 2008 , Samuel et al, 2015 , Cleland et al, 2010 , Shelton et al, 2011 ). Further, prior research has shown that neighborhoods with low social cohesion are related to an increase in adverse health outcomes and behaviors, such as depression and smoking ( Echeverría et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%